The significance of sonographically thickened endometrium in asymptomatic postmenopausal women - Runa Ozelci; Berna Dilbaz; Funda Akpınar; Tugba Kınay; Emre Baser; Oya Aldemir; Sadıman Kıykac Altınbas (Korean Society of Obstetrics and Gynecology, 2019)
ObjectiveTo investigate the correlation between sonographic, hysteroscopic, and pathological findings in postmenopausal asymptomatic patients with sonographically thickened endometrium.MethodsThe records of postmenopausal patients who attended the Menopause Outpatient Clinic of a tertiary women's hospital in Ankara, Turkey between January 1, 2012 and December 15, 2013 were retrieved. A total of 266 postmenopausal women without vaginal bleeding underwent hysteroscopic evaluation and endometrial sampling. Patients whose pathological records indicated an endometrial thickness equal to or greater than 6 mm (double layer) on transvaginal ultrasonography without any symptoms were included in the study.ResultsThe most frequently detected focal intrauterine lesions in asymptomatic women were endometrial polyps, which were diagnosed in 168 (63.1%) cases. Twenty-four (9%) patients were diagnosed as having simple hyperplasia, 4 (1%) atypical hyperplasia, and 8 (3%) endometrial adenocarcinoma. Two of the patients with adenocarcinoma were diagnosed based on endometrial polyps, and 6 cases showed endometrial hyperplasia on hysteroscopy, while histological examination showed endometrial carcinoma.ConclusionWe suggest 10.5 mm as the cutoff value for endometrial thickness and recommend hysteroscopy following dilatation and curettage to increase diagnostic efficacy and provide definitive treatment in asymptomatic postmenopausal women with thickened endometrium.